The Effect of Visual Thinking Strategies on Iraqi EFL Students` Communication Skills (Journal of the College of Education for Women, 2024)
The goal of the study is to find out the effect of the visual thinking strategies (VTS) upon the college students` achievement in English language communication skills. To achieve the aim of the study, the experimental posttest design is used. The sample is represented by (70) second stage learners at English Department at the College of Education. They were randomly chosen and divided into two groups: the experimental and control groups (35) students in each group. To achieve the aim of the study, an achievement test for communication skills has constructed and distributed to the sample of the study. The researcher has exposed the experimental group to the VTS, while the control group has taught the conventional way. The results show that VTS learners' scores on the posttest were statistically significant to the development in students ` achievement and in vocabulary and speaking skills. Drawing the conclusion, recommendations and suggestions for further studies are put forward.